Extraction, purification, structural features and biological activities of longan fruit pulp (Longyan) polysaccharides: A review - Yue, Xuan; Chen, Zhejie; Zhang, Jinming; Huang, Chi; Zhao, Shiyi; Li, Xuebo; Qu, Yan; Zhang, Chen (Frontiers in Nutrition, 2022)
Dimocarpus longan Lour. (also called as longan) is a subtropical and tropical evergreen tree belonging to the Sapindaceae family and is widely distributed in China, Southeast Asia and South Asia. The pulp of longan fruit is a time-honored traditional medicinal and edible raw material in China and some Asian countries. With the advancement of food therapy in modern medicine, longan fruit pulp as an edible medicinal material is expected to usher in its rapid development as a functional nutrient. As one of the main constituents of longan fruit pulp, longan fruit pulp polysaccharides (LPs) play an indispensable role in longan fruit pulp-based functional utilization. This review aims to outline the extraction and purification methods, structural characteristics and biological activities (such as immunoregulatory, anti-tumor, prebiotic, anti-oxidant, anti-inflammatory and inhibition of AChE activity) of LPs. Besides, the structure-activity relationship, application prospect and patent application of LPs were analyzed and summarized. Through the systematic summary, this review attempts to provide a theoretical basis for further research of LPs, and promote the industrial development of this class of polysaccharides.